New 2D–π–2A organic dyes with bipyridine anchoring groups for DSSCs. (25th March 2019) - Jia, Hai-Lang; Peng, Zhi-Jie; Gong, Bing-Quan; Huang, Cheng-Yan; Guan, Ming-Yun
Abstract : Two new 2D–π–2A-type organic dyes with bipyridine anchoring groups were synthesized and applied in dye-sensitized solar cells. Abstract : Anchoring groups play an important role in the structure of dyes by determining the charge injection efficiency and the bonding degree between the sensitizer and the semiconductor surface. In this work, two new 2D–π–2A-type metal-free organic dyesS1 andS2 with bipyridine anchoring groups were synthesized and applied in dye-sensitized solar cells (DSSCs). The IR spectra indicated that the two dyes could anchor on the Lewis acid sites of the TiO2 surface through the bipyridine anchoring group, and the bidentate configuration was conducive for improving the electron injection efficiency and enhancing the dye adsorption stability. In addition, since phenothiazine and carbazole are often used as electron donors in DSSCs, in this work, we also compared their different effects on the photoelectric properties in detail. The DSSC based onS1 showed PCE of 4.39% under AM 1.5G irradiation and V oc of 708 mV, J sc of 9.39 mA cm −2, and FF of 65.99%, while the DSSC based onS2 showed PCE of 2.96%; the main reason for these results is that their V oc and J sc values were very different. We also studied the dye loading amounts, optical properties, electrochemical properties, and photovoltaic performances to analyze the differences between the two devices.